Intellectual Capital and Long Term Competitive Advantage through Innovation Capability - Sugianto (Journal Economic Business Innovation, 2026)
Purpose: The focus of this study is to investigate how intellectual capital can generate sustained competitive advantage through innovation capability. Method: The variance-based structural equation modeling (VB-SEM) technique is utilized in this study to examine a mediation model guided by strategic management theory. Findings: We find that intellectual capital is an important strategic resource that positively influences firms’ capacity to create innovation capability and long-term competitive advantage. Innovation capability is a dynamic force to turn knowledge-based resources to competitive outcomes that last longer. The findings also indicate that the direct effect of intellectual capital to long-term competitive advantage is enhanced by firms' ability to utilize innovation-related capabilities, which stresses the importance of developing capabilities rather than merely possessing resources. In sum, the model offers strong empirical justification for the theoretical unification of resource-based and dynamic capability views when accounting for sustained competitive advantage. Novelty: This study provides a unique contribution by casting innovation capability as one composite mediator, which is an explicit link between intellectual capital and lasting competitive advantage consequently adding to existing research that has predominantly concentrated on short-term performance or fragmented measures of innovation. Implications: Findings The research offers strategic implications for managers and policy makers, because it demonstrates the significance of setting IC management in line with innovation capability development toward sustainability competitiveness on a knowledge-based industry.